Field Efficacy of Different IPM Modules Against Brinjal Shoot and Fruit Borer (BSFB) and The Sucking Insect Pests of Brinjal - Nayak, U. S.; Rath, L. K.; Baral, K.; Senapathy, S. (International Journal of Bio-resource and Stress Management, 2016)
Field experiments carried out to evaluate the efficacy of some IPM modules against Leucinodes orbonalis Guene on brinjal at Keonjhar district of Odisha during 2009–10 and 2010–11 were also assessed for their efficacy against the sucking insect pests of brinjal. The results indicated that the IPM module comprising of soil application of cartap hydrochloride 4 G @ 1 kg a.i. ha-1 at 2 weeks of transplanting, intercropping with coriander in 3:1 ratio, alternate foliar spray of indoxacarb 14.5 SC @ 1 ml l-1 of water and rynaxypyr 20 SC @ 0.35 ml l-1 of water at 10 days interval twice at vegetative stage and six times commencing from fruiting stage and regular collection and destruction of infested plant parts was found to be highly effective in minimizing the infestation of L. orbonalis and resulted in the highest mean fruit yield of 247.57 q ha-1. Whereas, the IPM module consisting of soil application of vermicompost @ 5 t ha-1, seedling root dip with solution of Azotobactor, Phosphorous solublising bacteria and Pseudomonas fluorescence, raising maize as barrier crop, alternate application of deltamethrin 2.8 EC @ 1 ml l-1 of water and spinosad 45 SC @ 0.35 ml l-1 of water at 10 days interval twice at vegetative stage and six times commencing with fruiting stage, foliar application of boron @ 0.25% Borax (one at vegetative stage and other after flower initiation stage) and regular destruction of infested plant parts afforded maximum control of whiteflies and jassids in brinjal. All the IPM modules significantly brought down pest infestation in brinjal, whereas the maximum pest incidence was observed in the farmers’ practice despite repeated application of insecticides.